Servant leadership : a journey into the nature of legitimate power and greatness - Greenleaf, Robert K.; Spears, Larry C., 1955- (New York : Paulist Press, 2002)
A collection of essays, articles, and talks, composed over the course of twenty years beginning in 1969, in which the author discusses the importance of developing and following leaders who strive to serve with skill, understanding, and spirit.
Includes index.
Adult
Keywords: Associations, institutions, etc. -- Management; Leadership; Organizational effectiveness; Associations -- Management; Leadership; Organizational effectiveness